On Holomorphic Solutions of the Darwin Equations of Motion of Point Charges - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The existence of holomorphic (in time) solutions of the nonrelativistic Darwin equations of motion of point charges is proved with the help of the Cauchy theorem.